2021
DOI: 10.3390/su132212445
|View full text |Cite
|
Sign up to set email alerts
|

Jellyfishing in Europe: Current Status, Knowledge Gaps, and Future Directions towards a Sustainable Practice

Abstract: Jellyfish are often described as a nuisance species, but as our understanding shifts to more ecosystem-based conceptions, they are also recognized as both important components of marine ecosystems and a resource for humans. Here, we describe global jellyfish fisheries and review production, fishing methods, and applications based on the existing literature. We then focus on future development of a European jellyfish fishery based on current and recent EU research initiatives. Jellyfish have been a staple food … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 81 publications
0
7
0
Order By: Relevance
“…E-based fishery management has been suggested to safeguard a comprehensive approach for the sustainability of jellyfish fisheries that will be positive. To ensure environmental sustainability, certain issues like habitat integrity, monitoring, by-catches, seasonality and the life cycle of products have to be taken into account so they can be managed [ 13 ]. This implies taking integrated approaches to include state-of-the-art fishing management strategies within ecological boundaries by integrating fishing along with other human actions, and preserving ecosystem stability and biodiversity with the necessary processes to ensure the stability of ecosystems and/or their services [ 48 ].…”
Section: Sustainability and Economic Relevancementioning
confidence: 99%
See 1 more Smart Citation
“…E-based fishery management has been suggested to safeguard a comprehensive approach for the sustainability of jellyfish fisheries that will be positive. To ensure environmental sustainability, certain issues like habitat integrity, monitoring, by-catches, seasonality and the life cycle of products have to be taken into account so they can be managed [ 13 ]. This implies taking integrated approaches to include state-of-the-art fishing management strategies within ecological boundaries by integrating fishing along with other human actions, and preserving ecosystem stability and biodiversity with the necessary processes to ensure the stability of ecosystems and/or their services [ 48 ].…”
Section: Sustainability and Economic Relevancementioning
confidence: 99%
“…The practice of eating cooked umbrella in salads has extended to other Asian nations such as Malaysia, Thailand and Japan. Europe is beginning to see this possibility [ 11 , 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…We can achieve an overview of just how numerous and important this marine resource is by studying reported data on the number of known species of jellyfish [31]. Edelist et al reported that there are approximately 400 species of Scyphomedusae [32]. Of these, Dawson et 92 species are Rhizostomatous [33].…”
Section: Introductionmentioning
confidence: 99%
“…Jellyfish blooms are a global natural phenomenon that is sometimes considered to be exacerbated by human activities (Purcell et al, 2007). Jellyfish are typically perceived as a nuisance, negatively affecting human interests such as coastal leisure, tourism, fisheries, aquaculture, power, and desalination plants (Purcell et al, 2007;Edelist et al, 2021). They also play an important role in marine ecosystems and can be considered as a boon for fishers, a valuable source of food and other products when harvested sustainably (Edelist et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Jellyfish are typically perceived as a nuisance, negatively affecting human interests such as coastal leisure, tourism, fisheries, aquaculture, power, and desalination plants (Purcell et al, 2007;Edelist et al, 2021). They also play an important role in marine ecosystems and can be considered as a boon for fishers, a valuable source of food and other products when harvested sustainably (Edelist et al, 2021). For all these reasons, understanding jellyfish swarm dynamics and tracking their origins are important.…”
Section: Introductionmentioning
confidence: 99%